The Effect of Puzzle and Clock-Drawing Therapy on Cognitive Function in Ischemic Stroke Patients - Aaz Abi Zikri; Asep Rusman (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: According to the World Stroke Organization (WSO), there are 13.7 million new stroke cases and around 5.5 million deaths due to stroke each year. Based on the results of the 2023 Indonesian Health Survey (SKI), the prevalence of stroke in Indonesia is 8.7%. Meanwhile, in DKI Jakarta, the prevalence of stroke based on diagnosis among people aged ≥15 years is 13.5%. The most common type of stroke is ischemic stroke, with an increasing prevalence reaching 87% of all stroke cases. Stroke generally occurs in middle-aged and elderly populations. Stroke patients often experience cognitive impairment.Objective: To determine the effect of puzzle and clock-drawing therapy on improving cognitive function in patients with ischemic stroke. Research Method: A quasi-experimental study using a one-group pretest–posttest design. The population in this study consisted of all ischemic stroke patients treated at Jakarta Islamic Hospital Pondok Kopi, totaling 34 patients. Research Result: The results showed a significant improvement in cognitive function before and after the administration of puzzle therapy and clock-drawing therapy. The majority of participants initially had mild cognitive impairment (88.2%), and after the intervention, most participants showed no cognitive impairment (70.6%). Data analysis using the paired sample t-test revealed a p-value of 0.001 with α = 0.005, indicating that puzzle and clock-drawing therapy had a significant effect on improving cognitive function in ischemic stroke patients, with a significant difference in mean scores before and after the intervention. Conclusion: Puzzle and clock-drawing therapy have a positive effect on improving cognitive function in ischemic stroke patients. It is recommended that nurses assist ischemic stroke patients in maintaining memory by providing puzzle and clock-drawing therapy, which can help enhance cognitive function.